2018
DOI: 10.1007/s11524-018-0296-9
|View full text |Cite
|
Sign up to set email alerts
|

Power Outage Preparedness and Concern among Vulnerable New York City Residents

Abstract: Power outages can impact health, and certain populations may be more at risk. Personal preparedness may reduce impacts, but information on power outage preparedness and risk perception among vulnerable populations is limited. We examined power outage preparedness and concern among New York City residents, including vulnerable populations defined as older adults (≥ 65 years), and respondents with household members who require assistance with daily activities or depend on electric medical devices. A random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…Our individual-level survey did not find evidence of socioeconomic differences in exposure, but provided some evidence for socioeconomic differences in preparedness, with less educated respondents less likely to be prepared for an outage. This is consistent with evidence that socioeconomic barriers may hinder preparing for outages ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our individual-level survey did not find evidence of socioeconomic differences in exposure, but provided some evidence for socioeconomic differences in preparedness, with less educated respondents less likely to be prepared for an outage. This is consistent with evidence that socioeconomic barriers may hinder preparing for outages ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 90%
“…Scientists have identified that the elderly are more vulnerable to climate-related stressors [ 180 ], though they tend to be better prepared for disasters than young people [ 181 ]. A lot of articles are trying to estimate the health risks of the older population [ 182 ] and their vulnerability [ 180 ] when exposed to natural disasters.…”
Section: Resultsmentioning
confidence: 99%
“…Allerdings waren weniger als 1 % auf Heimbeatmungsgeräte angewiesen; die meisten waren abhängig von einer externen Sauerstoffzufuhr [ 25 ]. Auch in den USA konnte gezeigt werden, dass gerade vulnerable Gruppen unzureichend auf derartige Ereignisse vorbereitet sind und insbesondere damit einhergehende Risiken nicht hinreichend ernst genommen werden [ 15 ].…”
Section: Vulnerable Gruppenunclassified